Perpaduan Pendidikan Formal dan Pesantren untuk Mencetak Generasi Emas 2045 - Wahyu Qomaruddin; Andi Asyhari (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Education is one of the main pillars in shaping a quality generation capable of facing future challenges. In Indonesia, educational challenges such as low quality, lack of job-relevant skills, and character issues among the youth require comprehensive solutions. One potential approach is the integration of formal education and pesantren (Islamic boarding schools). Formal education focuses on intellectual development and technical skills, while pesantren play a crucial role in shaping the character and spirituality of students. The synergy between the two can produce individuals who are not only academically intelligent but also possess strong character and are globally competitive. This study aims to explore how the integration of formal education and pesantren can shape a golden generation that is competent, virtuous, and adaptable to the changing times. A qualitative approach was used to analyze the implementation of this educational integration at SMAS Al-Hikmah 2, which has successfully combined these two systems. The findings indicate that the integration of formal education and pesantren can enrich students' learning experiences, optimally develop their potential, and shape an excellent generation in both academic and character aspects. This synergy is expected to support Indonesia's goal of achieving the